Fermentative characteristics, fungal population, and losses of forage sorghum silage BRS 658 treated with different additives (Research, Society and Development, 2023)
This study aimed to evaluate the fermentative profile, losses, dry matter recovery, and fungi population in forage sorghum silage treated with different additives. The design was completely randomized, with four replications and seven treatments, which were: 1) Control (C), whole-plant sorghum with no additives; 2) Microbial (M), whole-plant sorghum + microbial additive (0.2% of original matter); 3) Sugar (S), whole-plant sorghum + brown sugar (4.0% of original matter); 4) Microbial plus sugar additives (MS), whole-plant sorghum + microbial additive (0.2% of original matter) + brown sugar (4.0% of original matter); 5) Whey (W), whole-plant sorghum + whey (3% of original matter); 6) Microbial plus whey additives (MW), whole-plant sorghum + microbial additive (0.2% of original matter) + whey (3% of original matter); 7) Microbial plus sugar plus whey (MSW), whole-plant sorghum + microbial additive (0.2% of original matter) + brown sugar (4.0% of original matter) + whey (3% of original matter). Sorghum was cut 111 days after emergence and ensiled in polyvinyl chloride silos. The storage lasted 35 days, after that period, the silos were opened and submitted to analysis. The inclusion of additives in sorghum silage has shown no significant difference in fungal population, lactic acid production, and losses by gases and effluents. The use of microbial inoculant + brown sugar in the sorghum silage BRS 658 decreased the values ​​of ammoniacal nitrogen, pH, propionic, and butyric acid. The inclusion of brown sugar in the sorghum silage promoted an increase in soluble carbohydrates and greater recovery of dry matter.